Marina Garone Gravier - Diniz, Kollontai Cossich (InfoDesign, 2009)
Through the interview, Marina shares her experiences in a personal tone: difficulties, decisions, preferences, reminders. Since there are few studies, practical or research conducted in this area, the interview provides an overview of the many paths that can be traced by whom, since the typography, look at the indigenous languages. Are obvious possibilities for linkages between design and other knowledge areas as linguistics and art history, and the contributions of a research seems specific to the study design as a whole.